Multiuser OFDM Adaptive Resource Allocation Based on Differential Evolution Algorithm - Yangkun Zhu; Xinyu Da; Yapu Zhang (Dianxin kexue)
An improved subcarrier and power allocation algorithms based on differential evolution algorithm was proposed for the adaptive resource allocation problem of multiuser orthogonal frequency division multiplexing. Subcarrier allocation was first implemented to distribute the total power uniformly on each subcarrier. Then via adding the step of detecting and improving constraints to improve the differential evolution algorithm and using it to achieve power allocation with a fitness function of the user's fairness and system capacity. Computer simulation results show that the proposed algorithm can achieve high improvement of the system capacity under low complexity and maintaining the fairness among users, the effectiveness of the algorithm was verified.